Constraints Faced by the Farmwomen in Women Headed Households - K. Uma Rani (Journal of Agricultural Extension Management, 2025)
The role of women in agriculture has become all the more important with migration of farmers and the increasing number of women headed households. However, women, as producers, still remain largely invisible and unsupported; mainstream investments and development interventions tend to focus elsewhere and are often ineffective. This study on women headed households in Andhra Pradesh analyses the personal, socio-economic and extension related characteristics of women heading farm households, types of women-headed households, constraints they face and identifies solutions. Constraints expressed include nonavailability of labour, poverty and indebtedness, high cost of fertilizers and pesticides, limitations in getting credit etc. Some of the suggestions include ensuring supply of good quality seeds, fertilizers etc., by the government; labour exchange between households and villages during peak seasonal farm operations to overcome constraint of labour shortage, imparting training on income generating activities, etc. The study concludes that income generating activities like, dairy units, sheep rearing units, vermmicompost units and small business activities like mushroom units, leaf plate making and value addition to locally available products may be encouraged to improve income levels and economic status of women. Women headed households deserve special attention within the ongoing developmental schemes so as to mainstream their concerns